Nilai Objek Wisata Air Terjun Way Lalaan Provinsi Lampung Dengan Metode Biaya Perjalanan (Travel Cost) - Jenny Sartika Sihotang; Christine Wulandari; Susni Herwanti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Attraction Waterfall Way Lalaan is one form of environmental services are less developed but has significant economic potential if managed properly. It is therefore necessary to study with the aim of determining the value of the waterfall attraction Way Lalaan visitor characteristics and determine the effect on travel expenses. Benefits of the research results are used as consideration in future management of this attraction. The study was conducted in March-April 2013 with as many as 96 respondents with direct interviews with travel costs were proxied visitors. Determination results of visitor travel expenses will be tested using multiple linear analysis with Minitab 16 software.The results showed the cost of travel for visitors Rp16,284,500/orang/kali visit. The average cost of a trip Rp 203,104 person/visit. Recreational value of Rp. 487,449,600/year. Variables outside the province, age and marital status simultaneously have a real influence on the cost of the trip. The value of the standard deviation (S) is Rp 151,589. The amount of influence the dependent variables simultaneously (R-Sq) was 61.9% and R-Sq (adj) which means the amount fluctuates depending on the variables influence the correlation of independent variables were added to a dependent variable is equal to 54.8%, while 45.2 % influenced by other variables. Keywords: falls value, multiple regression analysis, travel costs, Way Lalaan waterfall